Organisation isomorphism as determinants of environmental management accounting practices in Malaysian public listed companies / Aliza Ramli, Fatin Nabilah Abd Razak and Zarinah Abdul Rasit - Ramli, Aliza; Abd Razak, Fatin Nabilah; Abdul Rasit, Zarinah (Faculty of Accountancy, 2019)
Rising environmental issues due to companies’ activities and the public’s demand for a better environment has caused companies to face pressures from their stakeholders. However, in Malaysia, the implementation level of environmental practices is still moderate among public listed companies. This study, therefore, examines the organisational isomorphism as the determinant of the extent of environmental management accounting practices by Malaysian public listed companies in the Main Market based on institutional theory. Coercive, normative and mimetic isomorphism were taken as the determinants of the extent of usage of environmental management accounting. Survey method was used where an online questionnaire for data collection was send to Malaysian public listed companies. Statistical analyses were used to analyze the variables. The survey results revealed that these companies to a great extent have implemented environmental management accounting. It was also found that coercive isomorphism significantly influenced the environmental management accounting practices of Malaysian public listed companies. This suggests that companies will implement environmental-related practices with the existence of coercive pressures, derived from the government and the company’s shareholders. The implementation of environmental management accounting is beneficial to overcome the problem of traditional management accounting which fails to incorporate environmental hidden costs. Thus, the empirical findings from the study put forth the crucial specific factors that can aid the government to encourage companies to become responsible and contribute to green initiatives through environmental management accounting practices.